The Effect Of Live Streaming Selling And Product Quality On Women's Fashion Repurchase Interest At Shopee - Arivia Ananda; Koerniawan Hidajat (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
Online selling is nothing new in today's marketing system. Many people have been shopping online since they became familiar with the internet, so after the pandemic ended, people are already too comfortable with shopping online. In buying and selling products, the most common transaction is social networks such as Shopee because this application makes it easy for sellers to have a web page that can be connected to share information and communicate between sellers and buyers. Live Streaming has become a new trend in online shopping and the high competition for product quality is something that must be considered by sellers. The purpose of this study is to determine and explain the effect of live streaming selling and product quality on repurchase interest in women's fashion at Shopee. This research uses quantitative methods. Collecting questionnaire data with a Likert scale and using SmartPLS (Partiqal Least Squares) software to analyse the data. The results showed that live streaming sales affect repurchase intention and product quality does not affect repurchase intention in fashion products at Shopee.